Pendampingan dan Pemantapan Promosi Produk pada Kegiatan Live Selling Expo UPPKA Gadis Cemara Indah, Wanita Mandiri, Raja Muda Perwakilan BKKBN Provinsi Bengkulu - Erwani Yusuf; Hilyati Milla; Rossa Ayuni; Duharman Duharman (Gapenas Publisher, 2022)
The purpose of this activity is so that UPPKA groups can understand online sales, so it is necessary to be trained and accompanied by doing online marketing. Usually in online sales the duration of promotions is limited to a small amount of time, for that is why learn to pack the product promotion as well and effectively as possible so that buyers want to buy because they understand the composition and usefulness of the products sold. This sales promotion activity carried out live selling is expected to be sustainable for other groups, so that the UPPKA group built by BKKBN can be known by the people of Bengkulu in particular and the people of Indonesia in general